Response of Brassica napus to Plasmodiophora brassicae Involves Salicylic Acid-Mediated Immunity: An RNA-Seq-Based Study - Galindo-González, Leonardo; Manolii, Victor; Hwang, Sheau-Fang; Strelkov, Stephen E. (Frontiers in Plant Science, 2020)
Clubroot, caused by the obligate parasite Plasmodiophora brassicae, is an important disease of the Brassicaceae and poses a significant threat to the 26.7 billion canola/oilseed rape (Brassica napus) industry in western Canada. While clubroot is managed most effectively by planting resistant host varieties, new pathotypes of P. brassicae have emerged recently that can overcome this resistance. Whole genome analyses provide both a toolbox and a systemic view of molecular mechanisms in host-pathogen interactions, which can be used to design new breeding strategies to increase P. brassicae resistance. We used RNA-seq to evaluate differential gene expression at 7, 14 and 21 days after inoculation (dai) of two B. napus genotypes with differential responses to P. brassicae pathotype 5X. Gall development was evident at 14 dai in the susceptible genotype (the oilseed rape ‘Brutor’), while gall development in the resistant genotype (the rutabaga (B. napus) ‘Laurentian’) was limited and not visible until 21 dai. Immune responses were better sustained through the time-course in ‘Laurentian’, and numerous genes from immune-related functional categories were associated with salicylic acid (SA)-mediated responses. Jasmonic acid (JA)-mediated responses seemed to be mostly inhibited, especially in the resistant genotype. The upregulation of standard defense-related proteins, like chitinases and thaumatins, was evident in ‘Laurentian’. The enrichment, in both host genotypes, of functional categories for syncytium formation and response to nematodes indicated that cell enlargement during P. brassicae infection, and the metabolic processes therein, share similarities with the response to infection by nematodes that produce similar anatomical symptoms. An analysis of shared genes between the two genotypes at different time-points, confirmed that the nematode-like responses occurred earlier for ‘Brutor’, along with cell metabolism and growth changes. Additionally, the susceptible cultivar turned off defense mechanisms earlier than ‘Laurentian’. Collectively, this study showed the importance of SA in triggering immune responses and suggested some key resistance and susceptibility factors that can be used in future studies for resistance breeding through gene-editing approaches.